2014
DOI: 10.1007/s00264-014-2307-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes comparing Triathlon versus Duracon total knee arthroplasty: does the Triathlon outperform its predecessor?

Abstract: Purpose Total knee arthroplasty (TKA) prosthesis designs are constantly evolving to obtain greater functional performance. The aim of this study is to compare the functional outcomes between the newer single radius (SR) Triathlon prosthesis with its multiradius (MR) predecessor the Duracon. Method We analysed 1,012 primary TKA procedures which used either the Triathlon SR prosthesis or the Duracon MR prosthesis (338 Triathlon, 674 Duracon). Patients were assessed using the Knee Society score (KSS), range of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…Furthermore, Luo et al [32] found less anterior knee pain and painless crepitation among the SR group in the long-term follow-up study of a minimum of 10 years. These studies are supported by the fact that better functional outcomes of SR have been observed in many of the large study groups with long-term follow-up period [33,34]. In contrast, others ask whether these theoretical benefits of SR designs actually correlate with superior postoperative functional outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, Luo et al [32] found less anterior knee pain and painless crepitation among the SR group in the long-term follow-up study of a minimum of 10 years. These studies are supported by the fact that better functional outcomes of SR have been observed in many of the large study groups with long-term follow-up period [33,34]. In contrast, others ask whether these theoretical benefits of SR designs actually correlate with superior postoperative functional outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, a study by Palmer et al [9] compared the functional outcome of using a Triathlon prosthesis versus a Duracon prosthesis. Palmer et al analyzed KSS objective and functional scores 2-years post-operatively for 1012 primary TKAs (n = 338 Triathlon and 674 Duracon prostheses).…”
Section: Discussionmentioning
confidence: 98%
“…Few studies have extensively compared the SR and MR femoral components, and most of which focused on the clinical scores and ROM 11 12 13 14) . It is difficult to find studies that include preoperative or sequential follow-up data on quadriceps strength assessed in an objective manner 12) .…”
Section: Introductionmentioning
confidence: 99%